Lipase production by solid‐state fermentation of olive pomace in tray‐type and pressurized bioreactors. Issue 5 (7th December 2017) - Oliveira, Felisbela; Salgado, José Manuel; Pérez‐Rodríguez, Noelia; Domínguez, José Manuel; Venâncio, Armando; Belo, Isabel
Abstract: BACKGROUND: Bioreactor type, sterilization and specific operational conditions are key factors for the scale‐up of solid‐state fermentation (SSF). This work deals with the lipase production by SSF of olive pomace (OP) in traditional tray‐type and pressurized bioreactors. Important aspects of SSF in bioreactors were studied, such as the need for sterilization and moisture content (MC) control. RESULTS: At larger scale, there was no significant difference in lipase production between sterilized and unsterilized substrates, but MC control had significant impact. The production of lipase in a pressurized bioreactor, under air absolute pressure of 200 kPa and 400 kPa, was 2‐fold higher than in a tray‐type bioreactor using the same amount of substrate (500 g) and the same bed height. The protein content of substrate increased from 10 to 18% (w/w) after SSF and the fermented solid presented an antioxidant activity of 10 mmol Trolox kg ‐1 . CONCLUSIONS: SSF in a pressurized bioreactor enabled efficient production of lipase with higher substrate bed height in contrast to that in a tray‐type bioreactor. The improvement in nutritional value of the substrate by SSF indicates its potential applicability in animal feed. © 2017 Society of Chemical Industry